지역난방 2차측 공급수 온도 제어방안(설정온도 제어, 외기온 보상제어, 외기온 예측제어)에 따른 에너지사용량 실증 비교 - 조성환(Sung-Hwan Cho); 홍성기(Seong-Ki Hong); 이상준(Sang-Jun Lee) (설비공학 논문집, 27(3), 2015)
In this study, the actual energy consumption of the secondary side of District Heating System (DHS) with different hot water supply temperature control methods are compared. Three methods are Set-point Control, Outdoor Temperature Reset Control and Outdoor Temperature Prediction Control. While Outdoor Temperature Reset Control has been widely used for energy savings of the secondary side of the system, the results show that Outdoor Temperature Prediction Control method saves more energy. In general, Outdoor Temperature Prediction Control method lowers the supply temperature of hot water, and it reduces standby losses and increases overall heat transfer value of heated spaces due to more flow into the space. During actual energy consumption monitoring, Outdoor Temperature Prediction Control method saves about 7.1% in comparison to Outdoor Temperature Reset Control method and about 15.7% in comparison to Set-point Control method. Also, it is found that at when partial load condition, such as daytime, the fluctuation of hot water supply temperature with Set-point Control is more severe than Outdoor Temperature Prediction Control. Therefore, it proves that Outdoor Temperature Prediction Control is more stable even at the partial load conditions.